THE IMPACT OF COMPANY TRANSPARENCY ON THE PERFORMANCE OF PUBLIC LISTED COMPANIES IN MALAYSIA - Kavitha A/P Manoharan; Azahari Jamaludin; Rosmawati Deraman; Noor Azura Ahmad Shauri (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Transparency is crucial for financial, corporate social responsibility, and corporate governance, fostering company performance and sustainability. The study examines transparency’s effect on firm performance, offering insights on how transparent reporting methods can improve financial performance. It’s pertinent to Malaysia’s corporate sector, especially PLCs, clarifying the significance of transparency in enhancing stakeholder confidence, trust, and financial performance. The study benefits officials, regulators, and investors advancing sustainable development in Malaysia by informing policies and regulations promoting transparent reporting practices in Malaysian PLCs. The study’s contribution to knowledge, applicability, and potential influence on investment and policy choices enhance its significance.